Implementing Word Card Media Using Kahoot! to Improve English Reading Comprehension - Asti Yuniersi; Ahyadi Ahyadi; Hustiana Hustiana; Fajriani Fajriani; Dwi Adi Nugroho (Innovations in Language Education and Literature, 2026)
This study determined the effectiveness of word card media using Kahoot! on Class VII students' reading comprehension at SMPN 4 Majene and investigated their perceptions. A true-experimental design was employed with two intact classes (  each) selected via cluster random sampling. Data were collected through reading pre-/post-tests and a 10-item questionnaire administered to a purposive subsample of the 10 highest-scoring experimental students. Results revealed that the experimental class post-test mean (73.72) significantly exceeded the pre-test mean (31.92), with an N-Gain mean of 61.41. The independent samples t-test confirmed a statistically significant difference ( ), validating  . Additionally, the high-achieving subsample demonstrated positive perceptions (mean = 66.8), strongly agreeing that the media improved text comprehension, boosted confidence in group discussions, and enhanced learning satisfaction. Thus, word card media integrated with Kahoot! is highly effective for junior high school EFL reading instruction, although these perception findings are localized to top-performing learners and cannot be generalized to the entire class.